Characterization of the structure, thermal stability and wettability of the TiO2 nanotubes growth on the Ti-7.5Mo alloy surface - Chaves, J. M. [UNESP]; Escada, A. L.A. [UNESP]; Rodrigues, A. D.; Alves Claro, A. P.R. [UNESP] (Elsevier, 2016)
In this study, the Ti-7.5Mo experimental alloy for biomedical applications was processed showing orthorhombic (α″) martensite phase and low elastic modulus (54 GPa). The surface treatment permitted the growth of ordered TiO2 nanotubes via anodization process. The heat treatment during in situ Raman measurement revealed that the TiO2 nanotubes were transformed of the amorphous state for crystalline (anatase phase) around 400°C. Annealing of the nanotubes was evaluated by XRD, SEM and Raman spectroscopy. Results showed a high stability of the nanostructure, since only for temperatures above of 500°C, at which the phase rutile appears, the nanostructure tends to vanish. It was observed in Raman analysis an increasing of the average size of the crystallite of the anatase phase with annealing temperature ranging from 6.5 nm up to 13 nm, besides of the precipitation of the layer rutile in the interface nanotubes-substrate. It is believed that the contact between anatase crystallites or layer rutile of the interface lead to growth of the rutile phase, causing coalescence and subsequent collapse of the tubular nanostructure. The wettability, as well as, surface energy was dependent of the crystalline structure and morphology, becoming more hydrophilic in the anatase phase when as compared with amorphous and rutile phase. The typical features of the surface together excellent bulk properties (low elastic modulus) of the Ti-7.5Mo alloy can provide a guideline for future biomedical applications.
Keywords: Average size crystallite; Phase transformation; Ti-7.5Mo alloy; TiO2 nanotubes